Customer Relationship Management and Customer Loyalty on E-Commerce Platforms - Bunga Hidayatul Aini; M. Ikhwan Mansyuri; Risca Ariska Ramadhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effects of Customer Relationship Management (CRM) strategies, consisting of service personalization, two-way communication, and after-sales service, on customer loyalty in the e-commerce industry. The study hypothesizes that these three CRM dimensions positively affect customer loyalty. Research Method: This research used a quantitative approach focusing on customer transaction activities on e-commerce platforms. The population consisted of active e-commerce customers, with a sample of 97 respondents determined using Cochran’s formula. Primary data were collected through a 5-point Likert-scale questionnaire, supported by observation, documentation, and semi-structured interviews. Data were analyzed using multiple linear regression with SPSS version 21. Results and Discussion: The findings show that service personalization, two-way communication, and after-sales service have positive and significant effects on customer loyalty, both partially and simultaneously. After-sales service is the most dominant factor influencing loyalty. The three CRM dimensions explain 49.6% of the variation in customer loyalty, indicating that CRM strategies play an important role in retaining e-commerce customers. Implications: E-commerce companies should strengthen post-purchase services while maintaining personalized services and interactive communication to reduce customer switching. Originality: This study highlights the dominant role of after-sales service within CRM strategies in building customer loyalty in e-commerce.